Обґрунтування стратегії технічного розвитку підприємства в рамках екологічної політики - Бендина, Ольга Вікторівна; Буйниченко, Карина Олегівна; Літвиненко, Марія Владиславна (НТУ "ХПІ", 2015)
Обґрунтовано стратегію технічного розвитку підприємства в рамках екологічної політики ПАТ «Харківська ТЕЦ-5». Визначено за доцільне підтримувати наявну техніко технологічну базу шляхом проведення капітального ремонту устаткування та технічного доозброєння підприємства. У межах обраної форми технічного розвитку підприємства пріоритетним є напрямок підвищення ефективності функціонування (продуктивності праці) ремонтних служб ПАТ «Харківська ТЕЦ-5». Резерви зростання продуктивності праці необхідно визначати протягом кожного періоду часу за можливим використанням на конкретному підприємстві чи в галузі досягнень науки і техніки, організації суспільного виробництва, соціального розвитку.

Provided theoretical substantiation of economic management technical development. Analyzed changes in the enterprise JSC "Kharkiv TES-5" that took place in recent years in the following areas: logistical, organizational, economic. Human and human impacts on the environment in the area of the impact and JSC "Kharkiv TES-5" is within acceptable standards. The main factors that have a negative impact on the environment in JSC "Kharkiv TES-5": availability of resource and energy intensive processes and process equipment, equipment; depreciation of certain fixed assets and transport infrastructure; amortization depreciation of water supply networks is 40%, stormwater - 45% and sewerage networks - 30%; lack of effectiveness of the environmental management system in the field of environmental protection, regulation of natural resources. The strategy of technical development within the company environmental policy JSC "Kharkiv TES-5". Determined appropriate to maintain the existing techno-technological base through the overhaul of technical equipment and doozbroyennya company. Within the chosen form of technical enterprise development is a priority direction of improving the functioning (productivity) repair services JSC "Kharkiv TES". Provisions productivity growth should be determined for each period for possible use at a particular company or in the field of science and technology, organization of social production and social development.
Justification technological development strategy within the company environmental policy
Keywords: середовище навколишнє; знос; ремонт; електростанція теплова; захист довкілля; demolition; repair service company